Lactic Acid Yield Using Different Bacterial Strains, Its Purification, and Polymerization through Ring-Opening Reactions - F. G. Orozco; A. Valadez-González; J. A. Domínguez-Maldonado; F. Zuluaga; L. E. Figueroa-Oyosa; L. M. Alzate-Gaviria (International Journal of Polymer Science)
Laboratory-scale anaerobic fermentation was performed to obtain lactic acid from lactose, using five lactic acid bacteria: Lactococcus lactis, Lactobacillus bulgaricus, L. delbrueckii, L. plantarum, and L. delbrueckii lactis. A yield of 0.99 g lactic acid/g lactose was obtained with L. delbrueckii, from which a final concentration of 80.95 g/L aqueous solution was obtained through microfiltration, nanofiltration, and inverse osmosis membranes. The lactic acid was polymerized by means of ring-opening reactions (ROP) to obtain poly-DL-lactic acid (PDLLA), with a viscosity average molecular weight (Mv) of 19,264 g/mol.